Historical Semantics in the Word “Slander” in the al-Qur’an - Pohan, M. Riduan; Hadi, Syofyan (Jiluna Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
Semantic studies of the al-Qur’an play an important role in understanding the deep meaning of the vocabulary used in the divine revelation. One important approach in this study is Toshihiko Izutsu’s semantic approach, which examines key terms in the al-Qur’an to reveal the worldview (weltanschauung) contained therein. This study focuses on the semantic analysis of the word “slander” which is often used in everyday life but has narrowed its meaning in the general context of society. Izutsu’s approach involves synchronic and diachronic analysis of key terms to explore changes in meaning from the pre-Qur’anic, Qur’anic, to post-Qur’anic periods. The results of the study show that the word “slander” lexically comes from a root word meaning “to burn” or “to test the purity of metal”, which then develops in the al-Qur’an into various meanings such as a test of faith, polytheism, torture, and persecution. In the contemporary context, the meaning of slander has expanded to include acts of social injustice, hoaxes, and political tension. Through Izutsu’s approach, it can be understood that “slander” in the Qur’anic worldview is a divine selection process to test the quality of human faith, as well as being a description of the ethical, social, and spiritual interactions of humanity within the framework of the Qur’anic worldview.